On the Solitary Wave Solutions to the (2+1)-Dimensional Davey-Stewartson Equations - Ismael, Hajar F.; Bulut, Hasan (Springer International Publishing Ag, 2020)
In this article, by using the Bernoulli sub-equation, we build the analytical traveling wave solution of the (2+1)-dimensional Davey-Stewartson equation system. First of all, the imaginary (2+1)-dimensional Davey-Stewatson system is transformed into a system of nonlinear differential equations, After getting the resultant equation, the homogeneous method of balance between the highest power and the highest derivative of the ordinary differential equation is authorized and finally the outcomes equations are solved in order to achieve some new analytical solutions. Wolfram Mathematica Package is used for different cases as well as for different values of constants to investigate the solutions of the resulting system of a nonlinear differential equation. The results of this study are shown in 2D and 3D dimensions graphically.
4th International Conference on Computational Mathematics and Engineering Sciences (CMES) -- APR 20-22, 2019 -- Akdeniz Univ, Antalya, TURKEY
Keywords: Bernoulli sub-equation; Davey-Stewatson equations